Kajian Daya Dukung Lahan dan Kualitas Pengalaman Wisatawan: Integrasi Faktor Lingkungan dalam Pengembangan Desa Wisata Antiga, Kabupaten Karangasem - Suprapto, I Nyoman Arto; Moh. Agus Sutiarso; I Nyoman Triana Putra (LPPM STP ARS Internasional, 2024)
Antiga Tourism Village has various potential tourist attractions, especially marine and hilly nature tourism, namely the Labuan Amuk Beach area which has a variety of coral reefs and Batu Belah hill that present hill views. In line with the policy of the Karangasem Regency Government, some areas that have potential tourist attractions must be synergized with existing local potential, such as culture, agriculture, or other resources should be developed with a sustainable tourism approach. This study examines how to develop natural tourism by utilizing GIS technology in tourist villages to analyze the carrying capacity of the area in supporting tourism activities. This research was conducted with a quantitative approach where data was obtained through a literature study process, institutional surveys, observations, and interviews. The data obtained were then coded so that they could be entered and analyzed in the ArcMap (GIS) application. Furthermore, after the data was coded, a Land Capability Analysis (AKL)/overlay calculation was carried out to determine the physical carrying capacity of the tourist village area. The final result of this study is a land capability map for the development of tourist attractions and tourism supporting facilities in tourist villages. The results of the AKL/overlay analysis show that the land capability units (SKL) in Antiga Village are divided into 3, namely high land capability with an area of ??404.47 Ha (56%) distributed especially in Banjar Labuhan, Banjar Kelod, and Banjar Tengading, medium land capability with an area of ??188.04 Ha (26%) distributed in Banjar Seraya, Banjar Kaler and Banjar Ketug, and low land capability with an area of ??127.32 Ha (18%) distributed in Banjar Seraya, Banjar Ketug, and Banjar Tengading. Thus, the development of tourism support facilities in particular can be directed in Banjar Labuhan by considering the character and suitability of Labuhan Amuk marine tourism activities